2014
DOI: 10.1095/biolreprod.113.114447
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Nucleotide Metabolism and a Role for AMP in Modulating Flagellar Waveforms in Mouse Sperm1

Abstract: While most ATP, the main energy source driving sperm motility, is derived from glycolysis and oxidative phosphorylation, the metabolic demands of the cell require the efficient use of power stored in high-energy phosphate bonds. In times of high energy consumption, adenylate kinase (AK) scavenges one ATP molecule by transphosphorylation of two molecules of ADP, simultaneously yielding one molecule of AMP as a by-product. Either ATP or ADP supported motility of detergent-modeled cauda epididymal mouse sperm, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
(86 reference statements)
0
27
0
1
Order By: Relevance
“…A strikingly similar attenuated flagellar beat and impaired sperm hyperactivation was also seen in sperm lacking the sperm-specific catalytic subunit of PKA, Cαs [25]. Flagellar beat waveform features seen with Gsk3a null sperm were observed in membrane permeabilized sperm activated in the presence of AMP [32] and also in sperm lacking the nucleoside transport protein Slc29a (ENT1) [33]. Further studies with sperm from Gsk3a (-/-) null mice are required where quantitation of flagellar beat amplitude and frequency can be coupled to biochemical changes in null sperm.…”
Section: Discussionmentioning
confidence: 62%
“…A strikingly similar attenuated flagellar beat and impaired sperm hyperactivation was also seen in sperm lacking the sperm-specific catalytic subunit of PKA, Cαs [25]. Flagellar beat waveform features seen with Gsk3a null sperm were observed in membrane permeabilized sperm activated in the presence of AMP [32] and also in sperm lacking the nucleoside transport protein Slc29a (ENT1) [33]. Further studies with sperm from Gsk3a (-/-) null mice are required where quantitation of flagellar beat amplitude and frequency can be coupled to biochemical changes in null sperm.…”
Section: Discussionmentioning
confidence: 62%
“…10e–g ). AK8 has been shown to have high affinity for AMP in vitro 51 and localize to mouse sperm flagellar axonemes 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The observation that ADP can rescue the inhibitory effects of high ATP concentrations on flagellar beating 16 18 suggests that both ATP and ADP cooperatively regulate dynein ATPases. It has been also shown that adenosine monophosphate (AMP) incubated with ATP can mimic the modulatory effect of ADP alone on flagellar beat pattern 19 . The mechanism underlying this effect is not fully understood but explained in part by adenylate kinase (AK), which reversibly catalyses the reaction ATP + AMP ↔ 2 ADP and maintains balanced nucleotide pools to support ciliary beating 20 .…”
Section: Introductionmentioning
confidence: 99%
“…LHDC, an enzyme that catalyzes the reversible conversion of pyruvate to lactate with a concomitant production of NAD + needed for a rapid glycolysis, appears to have a key role in sperm capacitation thanks to the high concentration of pyruvate present in the female reproductive tract (Hereng et al ., ). Another enzyme that plays an important role in energy production and sperm motility in AK1; this enzyme, located in the flagellum, catalyzes the production of ATP using ADP as a substrate and thus provides an extra source of ATP needed to get slower and more fluid waves that propagate down the flagellum (Cao et al ., ; Vadnais et al ., ). Consequently, a reduction on the quantity or quality of those proteins both in the spermatozoa itself or in the prostasomes reservoir may have an extremely detrimental effect over fertility as it may compromise the sperm energy production.…”
Section: Discussionmentioning
confidence: 97%